Post stroke fatigue and its associated factors among stroke survivors in the second affiliated hospital of Guizhou University of traditional Chinese Medicine, China - Yuan, Dong (2025)
Post stroke fatigue (PSF) is a common and debilitating condition among stroke survivors, significantly affecting their quality of life (QoL), activities of daily living (ADLs), and recovery outcomes. Despite its clinical importance, the proportion and associated factors of PSF remain underexplored, particularly in young and middleaged stroke survivors. This cross-sectional study aimed to assess the proportion of PSF and its associated factors among 271 stroke survivors at the Second Affiliated Hospital of Guizhou University of Traditional Chinese Medicine, conducted from September 2023 to January 2024, using a convenient sampling method. Participants were included if they were aged 18 to less than 60 years, not bedridden, and had experienced a stroke within 3 months, while those with severe cognitive dysfunction or life-threatening comorbidities were excluded. Data were collected using validated instruments, including a sociodemographic characteristics questionnaire, the Fatigue Severity Scale (FSS), Short Version of the Stroke-Specific Quality of Life Scale (SV-SS-QoL), Patient Health Questionnaire-9 (PHQ-9), and Barthel Index (BI), and analyzed using SPSS version 29.0. The proportion of PSF among stroke survivors was 45.8%. Univariate analysis identified significant factors associated with PSF, including age, gender, income, education level, occupational status, living situation, depression, QoL, and ADLs. Multivariate logistic regression confirmed that age, gender, income, occupational status, depression, QoL, and ADLs were key factors. Middle-aged survivors (36–59 years) were 12.94 times more likely to experience fatigue compared to younger survivors (18–35 years) (OR 12.94, 95% CI: 1.91–87.83), and female survivors faced a 3.54 times higher risk of PSF compared to males (OR 3.54, 95% CI: 1.45–8.64). Depression significantly increased the likelihood of fatigue by 23% per unit increase in the depression score (OR 1.23, 95% CI: 1.13–1.34), while protective factors included higher income (OR 0.14, 95% CI: 0.04–0.53), stable occupational status (OR 0.09, 95% CI: 0.02–0.44), better QoL (OR 0.81, 95% CI: 0.75–0.86), and improved ADLs (OR 0.97, 95% CI: 0.95–0.98). The model demonstrated good calibration (Hosmer-Lemeshow test, χ² = 3.85, P = 0.87) and an accuracy of 85.2%. This study highlights the high proportion of PSF and its multifactorial associations in young and middle-aged stroke survivors. Identifying high-risk groups, such as middleaged individuals, females, and those with depression, is essential. Nurses can address PSF by providing psychological support, enhancing QoL and ADLs, and promoting income and occupational stability. These findings offer insights for developing personalized rehabilitation programs to alleviate PSF and improve recovery outcomes.